Strategies of formative assessment to improve reading comprehension: the evidence from the 8th grade learners - Xalmuratova , Shaxnozabonu Azat qizi (The Lingua Spectrum, 2026)
Reading comprehension is a critical skill that enables learners to comprehend, interpret, and analyze written materials. However, many middle school students struggle to understand complex literature. This article investigates the role of formative assessment procedures in enhancing reading comprehension among 8th-grade students. Formative assessment monitors students' learning during the teaching process and provides feedback to help them improve their comprehension. The study investigates at numerous formative assessment procedures used in the classroom, such as teacher feedback, questioning strategies, peer assessment, and self-assessment. These techniques enable pupils to think critically about what they read and become more engaged in the learning process. The study was undertaken with 8th-grade students to evaluate how different tactics influence their reading.